2004
DOI: 10.1084/jem.20040819
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Influence Monocytic GTPase Activity and Are Protective in Experimental Allergic Encephalitis

Abstract: In the chronic disabling disease multiple sclerosis (MS), migration of monocytes across the blood-brain barrier is a crucial step in the formation of new lesions in the central nervous system (CNS). Infiltrating monocyte-derived macrophages secrete inflammatory mediators such as oxygen radicals, which contribute to axonal demyelination and damage, resulting in neurological deficits. Flavonoids are compounds occurring naturally in food, which scavenge oxygen radicals and have antiinflammatory properties. To inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(115 citation statements)
references
References 25 publications
3
111
0
1
Order By: Relevance
“…While clinical disease is highly variable between patients with relapsing MS, the clinical course of the disease is surprisingly uniform in patients who have entered the progressive phase. Furthermore, onset of steady disease progression, both in patients with primary or secondary progressive disease, occurs around the same age (age [40][41][42][43][44][45][46][47][48][49][50], irrespective of previous disease severity or course [21,22].…”
Section: Oxidative Damage In Ms Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While clinical disease is highly variable between patients with relapsing MS, the clinical course of the disease is surprisingly uniform in patients who have entered the progressive phase. Furthermore, onset of steady disease progression, both in patients with primary or secondary progressive disease, occurs around the same age (age [40][41][42][43][44][45][46][47][48][49][50], irrespective of previous disease severity or course [21,22].…”
Section: Oxidative Damage In Ms Lesionsmentioning
confidence: 99%
“…Hence, antioxidant therapies might be a promising approach to counteract enhanced ROS levels and thus reduce disease progression. Indeed, experimental studies showed that exogenous antioxidants, such as flavonoids, a-lipoic acid [43,93] reduce disease symptoms in animal models of MS, however extremely high quantities are needed to observe beneficial effects. In contrast, well-designed clinical studies on antioxidant therapy in MS patients are rather limited.…”
Section: Therapeutic Strategies Aimed At Reducing Ros-mediated Injurymentioning
confidence: 99%
“…This finding indicates that these dietary compounds can interfere with inflammatory mechanisms. In addition, flavonoids and curcumin were shown to posses anti-inflammatory properties in EAE models (Natarajan & Bright, 2002;Hendriks et al, 2004), suggesting these compounds to have the ability to reduce MS disease activity. Furthermore, dietary fatty acids have immunoregulatory activity and the inflammatory process in autoimmune disease may be an important mechanistic target for these compounds to modulate disease activity (Harbige, 1998).…”
Section: Dietary Compounds Targeting Different Pathomechanisms In Msmentioning
confidence: 99%
“…Quercetin and epigallocatechin gallate (EGCG) reduce the production of proinflammatory cytokines by macrophages and microglia 142, 143, 144, 145. Moreover, flavonoids, such as quercetin, suppress the capacity of monocytes to cross the BBB and limit the uptake of myelin by macrophages 146, 147. Interestingly, quercetin was shown to suppress proinflammatory cytokine production by monocytes derived from MS patients 148.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Interestingly, quercetin was shown to suppress proinflammatory cytokine production by monocytes derived from MS patients 148. Moreover, quercetin, EGCG, and resveratrol reduce disease severity in the EAE model 147, 149, 150. In EAE, flavonoids mainly exert their beneficial effects through their anti‐inflammatory properties.…”
Section: Flavonoidsmentioning
confidence: 99%